Bromeliaceae: Profile of an Adaptive Radiation. D. H. Benzing. Cambridge University Press. 2000. 690pp. ISBN 0 521 43031 3. £80.00 (hardback). DOI: 10.10M/S0960428602240159 - HERBERT, J. (Edinburgh Journal of Botany, 2017)
..